Determinants of knowledge of HIV status in South Africa: results from a population-based HIV survey - Peltzer Karl; Matseke Gladys; Mzolo Thembile; Majaja Mmapaseka (BMC Public Health, 2009)
Abstract Background Over 30% of women and men in the South African national HIV household of 2005 indicated that they had previously been tested for HIV (of which 91% were aware of their test results). This paper seeks to describe the associations between socio-demographic, behavioural and social characteristics and knowledge of HIV status among a nationally representative population in South Africa. Methods A multistage probability sample involving 16395 male and female respondents, aged 15 years or older was selected. The sample was representative of the South African population by age, race, province and type of living area, e.g. urban formal, urban informal, etc. Respondents were interviewed on HIV knowledge, perceptions and behaviour and provided blood for research HIV testing. Bivariate and multivariate logistic regression was used to identify socio-demographic, social and behavioural factors associated with knowledge of HIV status. Results From the total sample 27.6% ever and 7.8% knew their HIV status in the past 12 months. In multivariate analyses being female, the age group 25 to 34 years old, other than African Black population group (White, Coloured, Asian), higher educational level, being employed, urban residence, awareness of a place nearby where one could be tested for HIV, impact of HIV on the household and having had two of more sexual partners in the past year were associated with knowledge of HIV status. Among HIV positive persons awareness of a place nearby where one could be tested for HIV and impact of HIV on the household were associated knowledge of HIV status, and among HIV negative persons HIV risk behaviour (multiple partners, no condom use), awareness of a place nearby where one could be tested for HIV, higher knowledge score on HIV and knowledge of serodiscordance were associated knowledge of HIV status. Conclusion Education about HIV/AIDS and access to HIV counselling and testing (HCT) in rural areas, in particular among the Black African population group needs to be improved, in order to enhance the uptake of HIV counselling and testing services, an essential step for the initiation of treatment.